Modification of Vigenere Algorithm and One Time Pad Using Rivest Code 6 (RC6) Key Expansion - Arif Budiman; Paradise Paradise (Compiler, 2019)
Information technology that is increasingly developing today must be balanced with the similarity of information data. Information security is obtained by applying cryptographic techniques, Vigenere Cipher is a key symmetry algorithm that uses a substitution technique that uses two letters encoding the original message. Vigenere cipher has a weakness because it uses short keywords and its use will be repeated. In this study, we will discuss the modification of the vigenere cipher algorithm and one time pad by adding a key elongation process as done in the RC6 algorithm. The results of the study will produce new variations in data security by combining the vigenere cipher algorithm and vernam cipher with key expansion algorithm RC6